Use of Percoll Density Centrifugation for Sperm sexing in Small Ruminants (Global Journal of Science Frontier Research, 2017)
Sperm sexing represents the most promising approach for production of gender-specific livestock under commercial settings Flow cytometry is currently the method of choice for sexing sperm cells but remains costly has low throughput and lowers fertility in vivo Thus the study was aimed to test Percoll density centrifugation for sexing sperm cells in small ruminants Semen from both rams n 4 and bucks n 4 was collected by electro-ejaculation cryopreserved and further used for Percoll density centrifugation PDC Sperm sexing was confirmed by Real-Time PCR by determining the ratio of X and Y-bearing sperm cells The semen before and after PDC in goats did not alter proportion of X-bearing 30 A vs 28 A 34 A vs 41 A 55 A vs 56 A 42 A vs 40 A or Y-bearing 70 A vs 72 A 66 A vs 59 A 45 A vs 44 A 58 A vs 60 A However semen from one ram was efficiently sexed by PDC for both X-bearing 46 A vs 62 B 37 A vs 34 A 52 A vs 54 A 60 A vs 70 A or Y-bearing 54 A vs 38 B 63 A vs 66 A 48 A vs 46 A 40 A vs 30 A In conclusion Percoll density centrifugation was effective for sexing sheep sperm cells but requires further improvements for its usage for small ruminants
Keywords: capra hircus; ovis aries; IVF; gender section; sexed semen